2014
DOI: 10.1080/02640414.2014.965191
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical determinants of acceleration and maximal sprinting speed in highly trained young soccer players

Abstract: The aim of the present study was to examine, in highly trained young soccer players, the mechanical horizontal determinants of acceleration (Acc) and maximal sprinting speed (MSS). Eighty-six players (14.1 ± 2.4 year) performed a 40-m sprint to assess Acc and MSS. Speed was measured with a 100-Hz radar, and theoretical maximal velocity (V), horizontal force (F) and horizontal power (P) were calculated. Within each age group, players were classified as high Acc/fast MSS (>2% faster than group mean), medium (bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 30 publications
6
111
0
3
Order By: Relevance
“…The differences in sprinting acceleration performance between sprinters and hurdlers may be more explained by differences in the mechanical effectiveness of force application between the events and especially by the ability to apply more effectively the force into the anteroposterior direction. These results are in agreement with previous studies that have revealed that highlevel athletes are able to horizontally apply higher forces upon contact with the ground (Morin et al, 2011;Buchheit et al, 2014;Kawamori et al, 2014;Pantoja et al, 2016;Jiménez-Reyes et al, 2018b).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The differences in sprinting acceleration performance between sprinters and hurdlers may be more explained by differences in the mechanical effectiveness of force application between the events and especially by the ability to apply more effectively the force into the anteroposterior direction. These results are in agreement with previous studies that have revealed that highlevel athletes are able to horizontally apply higher forces upon contact with the ground (Morin et al, 2011;Buchheit et al, 2014;Kawamori et al, 2014;Pantoja et al, 2016;Jiménez-Reyes et al, 2018b).…”
Section: Discussionsupporting
confidence: 93%
“…The horizontal F-V-P profile provides information for the specific sprint-acceleration motion, while the vertical F-V-P profile provides information for the maximal levels of force, and velocity of the neuromuscular system (Morin and Samozino, 2016). The F-V-P profile is able to distinguish differences in the mechanical properties of athletes from different sports, levels of practice, playing positions, age, and sex (Buchheit et al, 2014;Cross et al, 2015;Slawinski et al, 2017;Alcazar et al, 2018;Jiménez-Reyes et al, 2018a,b;Haugen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…No hemos encontrado ningún estudio que analice la fuerza horizontal en función de la edad en futbolistas. Un estudio realizado con jóvenes jugadores de fútbol afirma que la capacidad de generar fuerza en el eje horizontal puede tener implicaciones directas en la capacidad de sprintar, especialmente en distancias cortas (Buchheit et al, 2014). En este sentido sería interesante medir esta capacidad en jugadores de fútbol de distintas categorías con el fin de respaldar la idea de que los test de salto horizontal pueden ser un buen instrumento para analizar el rendimiento en categorías jóvenes y analizar si existe relación con la capacidad de generar fuerza en el eje horizontal.…”
Section: Discussionunclassified
“…A pesar de la importancia que tiene la fuerza en el componente horizontal (Ronnestad, Kvamme, Sunde & Raastad, 2008), son pocos los estudios que han analizado este aspecto en el fút-bol (Katis & Pellis, 2009;Ronnestad et al, 2008). Una investigación reciente realizada con jovenes futbolistas (14.1 ± 2.4 años) expone que mejorar la capacidad de producción de fuerza horizontal puede ser eficaz para mejorar el rendimiento de sprint en distancias cortas (Buchheit et al, 2014). Por tanto, pueden ser necesarios más estudios que analicen el salto horizontal (SH) en el fútbol haciendo una diferenciación por categorías, edades o niveles.…”
Section: Introductionunclassified
“…However, this is not always how power is used or computed in the literature. Specifically, sports biomechanists often split power into its 'components', as though it were a vector quantity; for example, reporting 'vertical' or 'horizontal' power (e.g., [47,48,49,50]). In a strict mechanical sense, these quantities are not real powers.…”
Section: Directional Powermentioning
confidence: 99%